A Study on the Reporting of Indian Muslim Women’s Problems in the Mainstream Media - Jothi, P Sri; Neelamalar, M (Journal of New Media and Mass Communication, 2015)
Today, literally hundreds of magazines, journals, newspapers, television channels, FM radio channels and new media deliver various kinds of information, about current affairs and events all around the world. These deal not simply with religion, but with social and political issues as well. These mass media publications have played a crucial role in promoting social and political awareness in the society and in getting people’s views and concerns across to the community, and to the state authorities, and in promoting closer interaction between nations. Apart from various social issues in the society, less importance is given to the news about women’s community. The challenge before the media is to move beyond clubbing what happens to women, with routine crime briefs, on the one hand, and sensational stories, on the other. And different women’s issues related to women and religion are not given much consequence; generally violence against women and sexual crimes are exaggerated to make interesting stories to attract commercially. Muslims in India are provided a separate civil code, and the Indian Constitution as well as administration recognizes the importance that should be given to the religion termed ‘minority’. Still, the feeling among Indian women in general and Muslim women in particular is that in matters such as multi-marriages allowed to Muslim men (it is illegal if the Hindu men do the same), the irregularities in the ‘divorce’ formalities and the injustice committed towards Muslim women by their husbands and families are not given proper consideration by the Indian mainstream media. Therefore, two renowned Indian newspapers ‘The Hindu and ‘The Times of India’ are taken and contextually analyzed regarding mass media reporting of Indian Muslim Women’s Issues.